Clarification influence upon sensorial and analytical characteristics of Muscat dry wine - Catherine Guillou; José Luis Aleixandre; Maria José García; Victoria Lizama (OENO One, 1998)
The influence of the clarification on the analytical and sensorial characteristics has been studied on a dry white wine of Muscat. To carry out this work, we have used dry wine of Muscat of the Valencia denomination of origin from the 1995 vintage. The clarification has been realized with four differents c1arifying agents: gelatin, blood albumin, casein and egg albumin associated with bentonite, used in two different doses: a medium doses, calculated from the lowest and highest doses recommended by the maker, and the lowest dose. The analysis physico-chemical have been made following the official methods of the Bulletin de l'Office Internationale de la Vigne et du Vin. The aromatic compounds (esters, high alcohols and terpenes), polyols were set by the gas chromatographie technique, with a chromatograph HEWLETT-PACKARD 5890 A, with a FID and an HP-3395, using nitrogen as carrier gas. Also the sensory characteristics have been determined. Each clarifying agent influence in different ways: gelatin and blood albumin affect fundamentaly the physico-chemical characteristics. Whereas egg albumin decreases the contents in esters, high alcohols, acetaldehide, and methanol. To a lesser extend, blood albumine and casein affect the aromatic fraction. The use of egg albumin isn't advisable for the clarification of white wines, anyway the blood albumin because there are changes in the characteristics in a visible way. At the sight of the results, the combination of gelatin and bentonite for the clarification of a Muscat wine gives a more valuated wine by the consumers. Finally, the clarification has not any influence on attributes evaluated in the sensorial analysis.